Factors Causing Low Interest in Learning Science in Elementary Schools - Aditya Hartini; Siti Faridah (Journal of Sustainable Development Science, 2022)
The purpose of this study was to determine the cause of the low interest of students in science subjects at SDN 5 Komet Banjarbaru. The method used in this study is a descriptive method which aims to describe or describe a situation in a place where it is now. The object of this research is the factor that causes the students' low interest in learning about science subjects at SDN 5 Komet Banjarbaru. The subjects in this study were the fifth grade students of SDN 5 Komet Banjarbaru who were used as a source of information needed in collecting research data. The population in this study amounted to 60 students and the sampling technique in this study used purposive sampling. The sample in this study were 20 fifth grade students at SDN 5 Komet Banjarbaru. Some students said that external factors caused the students' low interest in learning science subjects at the Komet 5 Banjarbaru State Elementary School 50% of the external factors caused the students' low interest in learning science subjects at the Banjarbaru 5 Komet State Elementary School, while 21% small external factors caused the low interest of students in learning science subjects at the State Elementary School 5 Komet Banjarbaru.